Rendezőelvek és etnoregionalizmus Magyarországon. Társadalmi reformterveink margójára - A. Gergely, András (Tér és Társadalom, 1989)
Any organized society can only develop if its internal energies make it possible. Tradition is one, perhaps one among the first to be mentioned, form of possibilities or conditions. Principles of a democratic state political order require–both for the macro and local societies or communities–that central and local governments consider the needs, interests, values and objectives of the locality. In this way the political power can assure its own legitimacy, can deserve the citizens' everyday indulgence and thereby the society becomes controlable. In the history of Hungarian society as well as of East-European political way of thinldng, there is, however, a very bad sort of tradition: that of the political conservatism. During the significant periods of Hungarian history, usually dictatorial ideas, disguised as democratic, gained ground and the representatives of power of the time usually referred to some enlightened liberal past, the continuity of revolutionary revival. From the time of the Hungarian reform period–the first third of the 19th century–survives the view, even in party attitudes, which not only proclaims the principle of 'progress at all price' but regards creating and preserving values and customs or respecting tradition as its own task. This value-preserving mentality is based on the examples and Western patterns or prototypes of human rights and it is not the conservative ('retrograde') supporter of the absolutist state in politics either but just the opposite: it doubts the omnipotence of state and party-state and refuses the external pressure of 'progress' tailored by politicians. The disintegrated social attitude, which suffers from the lack of solidarity and overwork, which is defensive concerning its own realm of values, has lost its self-assurance by now. As civil and political indocility increases, search for morals, norms of behavour, subjective motivations and small community values strengthens. And while the political power confirms itself by 'delegitimation' and 'apoligizes' by breaking with certain past, the old forms of conventions, tradition and unwritten laws are getting more and more popular among individual citizens' images of future. The crisis of crisis management and the lack of social consensus might be the reason for the willingness of the political administration, which is failing both on economic and political grounds, to make reform-steps: reform plans are elaborated one after the other and are also used by power machineries to search for 'viable' ideologies day after day. There is, however, one reform idea basically missing from among the more and more frequentiy elaborated economic, socio-political and other 'packets', one which acknowledges the ethnic and regional stratification of society. It is missing, because planners of the future themselves 'inherited' the kind of intellectual mentality which nurses meso- and macro-levei ideas instead of the 'reform' of communal relationships and local societies. Albeit instead of any social stratification objective it would be more pragmatic to consider the spatial pattern of Hungarian society as a basic formula and acknowledge that the system of horizontal relationships of cross-county ethnic communities, or the more economically acting profitability within a regional space as well as local societies articulate rural society more deeply than it has been imagined so far. The civil sphere of Hungarian society makes attempts to get out of the 'guardian democracy': it finds room for manifestation in a wide range of political actions and starts bargaining on local political platforms. The duality of society–power starts to get loose spectacularly : the monolith power is disintegrated and so is the pluralistic society which proved to be tolerant. Now, the traditional mentality and the value-conservative loyalty to the government–so far latently hidden among various interest-spaces and local identity-consciousnesses–start to oppose, stronger and stronger, the weakening totalitarian state. Therefore, it is not at all excluded that the political loyalty and the civil societal rationality are going to be transformed into representations of direct movements, single-target aspirations and pluralistic-democratic interests: local societies require the recognition of their identity and the 'idea of nation' may be replaced by the idea of belonging to a region, a district or a settlements. The principle of development that became autotelic, can be by now replaced by the noumenon interests of spatial and seftlement autonomy which may become the supporters of an 'organic modernization=the yeast of reviving Hungarian ethnic groups.